Seminole - Tieck, Sarah, 1976- (2015)
Informative, easy-to read text and oversized photographs draw in readers as they learn about the Seminole. Traditional ways of life, including social structure, homes, food, art, clothing, and more are covered. A map highlights the tribe's homeland, while fun facts and a timeline with photos help break up the text. Also discussed is contact with Europeans and American settlers, as well as how the people keep their culture alive today. The book closes with a quote from a tribe leader. Readers are left with a deeper understanding of the Seminole people. Table of contents, glossary, and index included.
Amazing people -- Seminole territory -- Home life -- What's they ate? -- Daily life -- Made by hand -- Spirit life -- Storytellers -- Fighting for land -- Back in time -- A strong nation.
Ages 7-10
Keywords: Seminole Indians -- History -- Juvenile literature; Seminole Indians -- Social life and customs -- Juvenile literature